Development of a tool to assess the compliance of cafeteria menus with the Mediterranean Diet - Silva, S. S. (2024)
Background: The Mediterranean diet (MD) has been considered one of the healthiest dietary patterns, and an excellent model of sustainability. Higher Education food services present an excellent scenario to encourage students healthy eating habits and modulate food choices. The purpose of this work was to develop an index to evaluate MD compliance with cafeteria menus. Methods: Three major axes were considered: MD key points, existing indexes on individual adherence to the MD, and existing indexes on menu assessment. The index includes four levels: (I) assesses the availability (IA), variety, and frequency (IB) of food; (II) evaluates the menu's nutritional quality; (III) assesses the menu's quality through information provided in the dishes' technical specifications and (IV) allows a more detailed evaluation through on-site visits and documentation consultation. The components receive a score between - 2 and 3, according to the given answers. The final score may vary between - 33.5 and 41.5 points depending on the degree of compliance with the MD key points. The index was applied to 60 menus from different contexts using complete assessments of each menu, performed independently by 3 researchers, using the same pre-prepared Microsoft Excel® spreadsheet. Inter-rater reliability was assessed using Cohen's Kappa and internal consistency with Cronbach's alpha. Results: Assessment for level I) returned a Cohen's Kappa coefficient of 0.92 (p < 0.05) and a Cronbach's alpha coefficient of 0.88. Dimension I is mostly influenced by subdimension IB (r = 0,97). The availability of non-starchy vegetables and fresh fruits has a stronger correlation with IA (availability of foods), and the higher availability of fish, pulses, and fruit has a strong positive correlation with IB (variety and frequency of foods). Conclusion: Researchers believe that the index is a useful tool to assess compliance of menus to the MD and help identify the key points that need to be addressed and improved in cafeterias.